Analysis of Barite Concrete as a Potential Neutron Radiation Shielding Material for BNCT Facilities - Rini Murtafi'atin; Widarto Widarto; Susilo Susilo; Ngurah Made Dharma Putra (Universitas Gadjah Mada, 2019)
This research aimed to determine the potential of barite concrete as a neutron radiation shielding material in the development of boron neutron capture therapy, by obtaining its neutron attenuation coefficient. Barite concrete samples were supplied by the Center of Accelerator Science and Technology in Yogyakarta, Indonesia. The experiment consisted of two parts, namely density analysis and determination of the neutron attenuation coefficient. For the latter, plutonium-beryllium was used as the neutron source, while a high purity germanium detector was used to measure the neutron radiation level. The results showed that barite concrete with a 2130 kg.m–3 density had a neutron attenuation coefficient of 0.0871 cm–3.